Expression Variability and Function of the RET Gene in Adult Peripheral Blood Mononuclear Cells. Issue 12 (December 2014) - Rusmini, Marta; Griseri, Paola; Matera, Ivana; Pontarini, Elena; Ravazzolo, Roberto; Mavilio, Domenico; Ceccherini, Isabella
<x xml:space="preserve">Abstract</x> RET is a gene playing a key role during embryogenesis and in particular during the enteric nervous system development. High levels of RET gene expression are maintained in different human tissues also in adulthood, although their physiological role remains unclear. In particular, collected evidences of a RET contribution in the development and maintenance of the immune system prompted us to investigate its levels of surface expression on peripheral blood mononuclear cells (PBMCs) from adult healthy donors. Despite variability among samples, RET expression was conserved at similar levels in the different immune cell subsets, with higher correlations in similar lymphocyte populations (i.e. CD4+ and CD8+ T cells). Conversely, no correlation was found between the amount of RET receptor, the expression of its putative ligands and co‐receptors and the genotypes at the RET locus. Moreover, we investigated the RET‐associated inflammatory pathways in PBMCs from healthy donors both in resting conditions and upon glial cell derived neurotrophic factor (GDNF) and GPI‐linked co‐receptors alpha 1 (GFRα1) mediated RET activation. RET mRNA levels positively correlated with the transcript amount of interleukin‐8 (IL‐8), a cytokine produced by monocytes and macrophages, though we could not demonstrate its direct effect on RET expression by in vitro experiments on THP1 human monocytic cells. These results imply that RET expression might be influenced by either cis‐ and/or trans‐factors, which together would account for its high variability within the general population, and suggest a putative functional role of the RET gene in modulating immune cell responses during inflammation and carcinogenesis. J. Cell. Physiol. 229: 2027–2037, 2014. © 2014 Wiley Periodicals, Inc.